Ureteropelvic obstruction and renal stones: etiology and treatment - Skolarikos, Andreas; Dellis, Andreas; Knoll, Thomas (Urolithiasis, 2015)
The simultaneous surgical management of ureteropelvic junction obstruction (UPJO) with concomitant renal stones has evolved the last 20 years; hence, the ideal minimally invasive technique is still controversial. Laparoscopic and robot-assisted laparoscopic operations allow precise surgical maneuvers and were thought to simplify the reconstruction steps of the procedure, especially in the treatment of complex cases with large stones. The aim of this study was to summarize the available perioperative and functional outcomes of minimally invasive available techniques. A non-systematic review of the literature was performed using a free-text protocol in the MEDLINE database. The terms used were “ureteropelvic junction obstruction,” “renal calculi” and “renal stones.” Furthermore, other significant relevant studies cited in the reference lists of the selected papers were also evaluated in the structure of this review. Currently, available evidence suggests that both laparoscopic and robotic-assisted techniques offer excellent surgical solutions in the field of UPJO reconstruction and renal stones removal. In the hands of experienced surgeons, laparoscopic and robotic pyeloplasty with concomitant stone removal is a safe procedure with high stone-free rates and UPJ patency. Minimally invasive pyeloplasty should constitute the first choice of treatment for concomitant renal stones and ureteropelvic junction obstruction.
Gesehen am 27.11.2018
Published online: 2 November 2014